The Role of Principal Leadership in Improving Ethical Techers Works of Islamic Education - Hernawan Hernawan; Subandi Subandi; Tukiran Tukiran (International Journal on Advanced Science, Education, and Religion, 2022)
This study aims to describe the principal's leadership role in increasing teacher morale, describe the principal's efforts to improve teacher work discipline, and describe the strategies employed by the principal to improve a good work ethic at IT Al Asror Middle School, Sekampung Case District in East Lampung District, Province Lampung. This study uses a type of qualitative research. The approach used is phenomenology. Data sources were taken from 4 people as informants. Data collection procedures include interview techniques, observation, and documentation studies. The results of research findings at IT Al Asror Middle School are: (1) The leadership role of the principal is to improve the teacher's work ethic in building student character, more importantly the principal provides motivation with a high spirit of intention to carry out his duties and responsibilities as a leader (2) Efforts carried out by the principal to improve the work ethic are compiling school programs, vision, mission and goals as well as evaluating the performance of teachers and employees, timely attendance, preparing lessons according to the lesson plan and the methods used in PAIKEM learning (3) the principal's strategy in improving the teacher's work ethic is to provide appropriate salaries, provide comfortable, clean and disciplined facilities in the school environment. The conclusion of this study is the leadership role of the school principal in improving the teacher's work ethic in building student character as a motivator, educator and motivator in providing good morale. tall and as a leader must create discipline, comfort, and high security in order to maintain the implementation of quality work in the school environment Keywords: Principal Leadership, Ethical Techers Works, Role of Principal Leadership